Mild Metal-Free 1,2-Dichlorination of Alkynes by NCS-PPh3-H2O System - Yuan, Jianan; Prakoso, Nurcahyo Iman; Morozumi, Tatsuya; Umezawa, Taiki (Synthesis, 2024)
Facile dichlorination of alkynes to give 1,2-dichloroalkenes is described. Previous studies for the synthesis of the 1,2-dichloroalkenes from the corresponding alkynes require stoichiometric amount of copper salt, preparation of the chlorinating reagent from hazardous compounds such as molecular chlorine, and highly acidic conditions. In this paper, only ubiquitous reagents, NCS-PPh3-H2O, are used to prepare the 1,2-dichloroalkenes from the alkynes under mild conditions. Various functional groups such as esters, ethers or carbamates were tolerated under these reaction conditions.
Keywords: dichloroalkene; chlorination; internal alkyne; terminal alkyne; NCS